Latex Dipping Machine PLC Control and Its Programming - Junxi Bi; Yimin Zhang; Yang Zhang (Institute of Advanced Engineering and Science, 2012)
Latex dipping machine is based on a latex patent products new-production condom and the development of the machine. The latex dipping agencies combined with production condom mechanism. First it realized a 3-dimensional accurate localization system using stepping motors. SIMATIC S7-200 series programmable controller, motion module EM253 and stepping motor are tied in wedlock to realize allocation of 3-dimension of X axis and Y axis and Z axis. Through the PTO pulse of Siemens S7-200 PLC controller and combined with the use of EM253 module, through the mould precise control programming soak glue and roll edge to achieve the control mold of rotation and swinging the uniform distributed latex. And the system has applied successfully in foreign-funded enterprise of Singapore. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1447